St. Joseph: depository of the mystery of god in the light of the Apostolic Exhortation “Redemptoris custos” - Soto Rivas, Víctor Pablo (2020)
The present article aims to reflect on the figure of St. Joseph as the depositary of the mystery of God in the light of Chapter II of the Apostolic Exhortation Redemptoris Custos (Custodian of the Redeemer) in order to re-evaluate the participation of this distinguished Patriarch in the plan of salvation because, as the pope´s document itself indicates: “…Joseph of Nazareth participated in this mystery like no other person, except Mary, the Mother of the Incarnate Word. He participated… committed to the reality of the same salvific act, being the depository of the same love… (RC 1). Above all, we will know in this article the participation of St. Joseph in the divine mystery as Spouse of Mary, virginal Father of Jesus and man of faith.